2015
DOI: 10.1128/genomea.00535-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Porcine Epidemic Diarrhea S Gene Indel Strain Isolated in France in December 2014

Abstract: We report the first and only case of a porcine epidemic diarrhea (PED) outbreak occurring in December 2014 in northern France, and we show using the full-length genome sequence of the French PED virus (PEDV) isolate that it was a PEDV indel strain close to German PEDV strains recently isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 9 publications
4
84
0
2
Order By: Relevance
“…The only well documented is a typical PED epidemic in Europe which occurred during the winter of 2005-2006 in Northern Italy [16]. Recently, the PED-confi rmed outbreaks have been reported in several Central European countries: Portugal [7], Germany [15], Austria [17], France [18], Belgium [19], Ukraine [20], Italy [21] and Slovenia [22]. The full genome sequencing of recent PEDV strains from Germany, Belgium and France [17][18][19] shows that they are all highly similar and closely related to S-INDEL strains from USA [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…The only well documented is a typical PED epidemic in Europe which occurred during the winter of 2005-2006 in Northern Italy [16]. Recently, the PED-confi rmed outbreaks have been reported in several Central European countries: Portugal [7], Germany [15], Austria [17], France [18], Belgium [19], Ukraine [20], Italy [21] and Slovenia [22]. The full genome sequencing of recent PEDV strains from Germany, Belgium and France [17][18][19] shows that they are all highly similar and closely related to S-INDEL strains from USA [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…23,41,55,[58][59][60][61][62]74,81,84,99,100 Those OH851-like variants, which belong to genotype Ib and are distributed in the People's Republic of China, the United States, South Korea, Japan, and Europe, have generally been associated with mildto-moderate clinical outbreaks. 15,20,21,56,57,81 However, severe cases associated with OH851-like strains were reported in Germany, where mortality in suckling piglets reached almost 70% in one of two sow farms, and in Portugal (mortality rate was not given). 16,22 A comparison experiment on the pathogenesis of three US prototype strains and one OH851-like variant reported recently by Chen et al 100 demonstrated that the OH851-like variant had significantly diminished clinical signs, virus shedding in feces, gross or histopathological lesions in small intestines, and immunohistochemistry (IHC) scores in ileum compared to three US prototype isolates.…”
Section: Clinical Signs Lesions and Pedv Replication Dynamics In Inmentioning
confidence: 99%
“…57,85 Possible recombination events might contribute to a rapid evolution of US strains. 57 Recently, OH851-like strains have been detected in South Korea 56 and Japan 81 in Asia, and Germany, 15,16 Italy, 17 the Netherlands, 18 Belgium, 19 France, 20 Portugal, 22 Slovenia, 21 and Austria 21 in Europe. A novel variant TC-PC22A (GenBank accession number KM392224), which has a large deletion (197-aa) in the N-terminal portion of the S protein, was recently isolated in the United States.…”
Section: Asiamentioning
confidence: 99%
See 2 more Smart Citations